Field Study on Sow Mortality in 15 Belgian Pig Farms - Caroline Bonckaert; Charlotte Brossé; Tamara Vandersmissen; Nermin Caliskan; Ellen Buys; Ilias Chantziaras; Dominiek Maes (Veterinary Sciences)
Sow mortality is a critical issue in intensive pig farming, impacting animal welfare, farm sustainability, and profitability. This study investigated the occurrence and causes of sow mortality on 15 Flemish sow farms, focusing on management practices, housing conditions, feeding strategies, and genetics. The average sow mortality rate across the farms was 11.4% in 2022, which decreased to 8.1% in 2023 following the implementation of targeted control measures. Necropsies performed on 100 deceased sows, coming from the 15 different farms, revealed that the primary causes of mortality were positional changes in internal organs (32%), arthritis (19%), and urogenital disorders (7%). Key recommendations to reduce sow mortality included optimizing sow health and body condition, improving housing and feeding management, and addressing genetic factors. The study highlights the multifaceted nature of sow mortality and the importance of a comprehensive approach to mitigate risks and improve sow welfare and productivity.